Use of white rot fungi in the degradation of an azo dye from the textile industry (2016)
Textile industry effluents—a complex mix of chemicals, among which colorants are of particular concern—impose great environmental challenges. In this study, a full 23 factorial design was used for determining the best conditions for the degradation of textile dye Basic Red 46 under solid state fermentation (SSF). Three white rot fungi Trametes versicolor, Pleurotus ostreatus, and Pleurotus pulmonarius were used in the fermentation process. A maximum degradation percentage of 63.0% was achieved at 17 days of incubation with T. versicolor under a moisture content of 90%, carbon to nitrogen ratio of 12: 1, and at 20°C. P. ostreatus and P. pulmonarius reached a maximum degradation percentage of 69.3% and 63.1%, respectively, after 25 days of fermentation. The scale-up of the fermentation process using T. versicolor led to a degradation percentage of 45.7% after 30 days of incubation. Additionally, the enzyme activity of laccase, manganese peroxidase and lignin peroxidase was measured. The results indicate that SSF offers a satisfactory degradation, whose efficiency depends on the optimization of process conditions.